(untitled) (Biological Sciences - PJSIR, 2019)
The current study was conducted to determine the antibacterial activity of 50 crude and processed honey samples produced by Apis mellifera and stingless bee. All the honey samples were collected from different places of Districts Dir, Swat and Oghi of Khyber Pakhtunkhwa Province, Pakistan and were tested against the six ATCC bacterial species including E. coli ATCC number 25922, Pseudomonas aeruginosa ATCC number 27853, Staphylococcus aureus ATCC number 6538, Enterococcus faecalis ATCC number 19433, Salmonella typhi ATCC number 19943 and Klebsiella pneumoniae ATCC number 27736. The honey samples showed variable zones of inhibition by using Agar well plate technique. E. coli showed 17-23 mm, S. typhi 31-37 mm, E. faecalis 28 mm, P. aeruginosa 14-15 mm, K. pneumoniae 20-24 mm and Staph. aureus 19-25 mm. Most of the honey samples used in this study showed broad spectrum antibacterial activity.